Dynamics of Judges’ Considerations in the Determination of Marriage Dispensation at the Enrekang Religios Court - Nur Alam, Nur Alam; Basri, Rusdaya; Fikri, Fikri (IAIN Parepare, 2020)
This study is the dynamics of judges' considerations in determining the dispensation of marriage at the Enrekang Religious Court. Ideally, the marriage is carried out in accordance with the existing provisions, but there are still opportunities provided by the state for the prospective bride and the family/guardian of the prospective bride and groom who still wish to have an underage marriage. Data in the Enrekang Religious Court that every year there is an increase in cases of marriage dispensation handled in the last 4 years. In 2017, there were 35 cases received, in 2018, there were 36 cases received, but in 2019 there were a surge in cases that were received by 42 cases, this was as a result of the enactment of Law No. 16 of 2019 and in 2020 as of July 10, 2020, 70 cases have been submitted. This type of study is a field research with qualitative research methods through juridical normative and sociological approaches. The results showed that 1) the inconsistency of the applicant’s expectations and the marriage dispensation request was not granted in accordance with the Enrekang Religious Court’s marriage dispensation decision, indicating that there was a social conflict contained in the stipulation, the petitioner continues to marry off her child to her future husband but is not registered at the Office of Religious Affairs or married in a series which will have a social impact because there is no recognition from the state, constraints in the management of population administration and others; 2) the factors considered by the judge in determining the dispensation of marriage at the Enrekang Religious Court are psychological, health, educational and economic factors, and 3) the dynamics in determining the dispensation of marriage at the Enrekang Religious Court can be seen in the determination of the dispensation of marriage, which differs from one case to another, because sometimes judges differ in giving legal considerations to a case, if there is a difference of opinion in a panel then a vote is made on the case.